Investigation on the application of worn cutting tool inserts as burnishing tools - Adiyaman, Oktay (Strojniški vestnik, 2024)
The amount of wear in cutting tools used in all machining processes is around 1 % to 2 % evaluation of the non-wearing areas of the inserts is economically beneficial. This study aims to test the usability of the non-wearing regions of the waste tungsten carbide (WC), cubic boron nitride (CBN) and ceramic inserts as a rolling tool in the deep rolling method and to observe their performance. The turned workpieces were deep rolled with three different types of waste-cutting tools (WC, CBN and ceramic) in different machining parameters (rolling force, number of passes, and feed rate). As a result, surface roughness and microhardness values obtained in deep rolling operations with these inserts were similar to those in deep rolling operations with other rolling tools. It has been determined that ceramic inserts perform better in deep rolling processes in terms of microhardness, and WC inserts perform better in terms of surface roughness. Thus, it has been determined that waste WC, CBN and ceramic inserts can be used in the deep rolling method.
Keywords: ball burnishing; deep rolling; gladilno valjanje s kroglo; globoko valjanje; integriteta površine; microhardness; mikrotrdota; površinska hrapavost; surface roughness; tribologija; tribology